Type 2 diabetes mellitus increases the risk of hepatocellular carcinoma in subjects with chronic hepatitis B virus infection: a meta-analysis and systematic review - Tan Y; Wei S; Zhang W; Yang J; Yang J; Yan L (Cancer Management and Research, 2019)
Yifei Tan,1 Shiyou Wei,2 Wei Zhang,1 Jian Yang,1 Jiayin Yang,1 Lunan Yan1 1Liver Transplantation Center, Department of Liver Surgery, West China Hospital of Sichuan University, Chengdu, Sichuan, China; 2Department of Thoracic Surgery, West China Hospital of Sichuan University, Chengdu, Sichuan, China Background: Type 2 diabetes mellitus has been proved to be a risk factor of hepatocellular carcinoma, but how diabetes affects incidence of hepatocellular carcinoma among patients with chronic hepatitis B virus infection remains controversial.Methods: A comprehensive search of Medline and Embase was performed. Incidence of hepatocellular carcinoma in chronic hepatitis B patients was the primary outcome. Pooled HRs and 95% CIs were calculated to assess the correlation between diabetes and incidence of hepatocellular carcinoma.Results: Five cohort studies and two case–control studies were identified, with a total of 21,842 chronic hepatitis B patients. The diabetes mellitus cohort was found to have increased incidence of hepatocellular carcinoma (pooled HR 1.77, 95% CI 1.28–2.47; fixed effect) and worse overall mortality (pooled RR 1.93, 95% CI 1.64–2.27; fixed effect) in comparison with those without diabetes. In case–control studies, hepatocellular carcinoma cases were found to have an insignificantly elevated diabetes mellitus rate in comparison with the control group.Conclusion: Type 2 diabetes mellitus is significantly associated with increased risk of hepatocellular carcinoma among patients with chronic hepatitis B virus infection, and aggressive management of diabetes mellitus is strongly suggested. Keywords: type 2 diabetes mellitus, hepatocellular carcinoma risk, HBV-infected